2022
DOI: 10.21203/rs.3.rs-1781582/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic Next-Generation Sequencing of Bronchoalveolar Lavage Fluid From Children With Severe Pneumonia in Pediatric Intensive Care Unit

Abstract: Background: Severe pneumonia due to lower respiratory tract infections (LRTIs) is a significant cause of morbidity and mortality in children. Noninfectious respiratory syndromes resembling LRTIs can complicate the diagnosis and may also make targeted therapy difficult because of the difficulty of identifying LRTI pathogens. In the present study, a highly sensitive metagenomic next-generation sequencing (mNGS) approach was used to characterize the microbiome of bronchoalveolar lavage fluid (BALF) in children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Multiple recent studies identified associations between the microbiome and immune responses to childhood vaccines, suggesting that microbial adjuvants could be used to promote robust vaccine responses among children [54][55][56][57][58]. Finally, next-generation sequencing holds substantial promise for the diagnosis of infectious diseases, as illustrated by recent studies that used this technology to identify potential causative pathogens among critically ill children with LRTI [59,60].…”
Section: Future Directionsmentioning
confidence: 99%
“…Multiple recent studies identified associations between the microbiome and immune responses to childhood vaccines, suggesting that microbial adjuvants could be used to promote robust vaccine responses among children [54][55][56][57][58]. Finally, next-generation sequencing holds substantial promise for the diagnosis of infectious diseases, as illustrated by recent studies that used this technology to identify potential causative pathogens among critically ill children with LRTI [59,60].…”
Section: Future Directionsmentioning
confidence: 99%